Breeding distribution and habitat selection of Red-breasted Mergansers in freshwater in western Norway - Råd, Olav (Wildfowl, 1980)
The breeding distribution and habitat selection of the Red-breasted Merganser Mergus serrator was investigated in west Norwegian freshwaters. The distribution is closely related to the distribution of the Three-spined Stickleback Gasterosteus aculeatus. The ducklings require small fishes, easily accessible in shallow waters. Stickleback is the only fish species in western Norway which fulfils these requirements. A female merganser selects her breeding habitat both from the structural characteristics of lakes and from quality and quantity of the food present for the young.